Configuration of the Supervised Curricular Internship in Physical Education – teaching degree: incursions and notes from Norbert Elias (Práxis Educativa, 2021)
This research sought to analyze the aspects related to the configuration of the Supervised Curricular Internship in the Physical Education Teaching Degree and its possible impacts on the pedagogical practice of the interns, based on the theoretical framework of Norbert Elias. The research was characterized as qualitative exploratory and had the participation of 61 people linked to the Supervised Curricular Internship. As a methodological strategy, the focus group and semi-structured interview were used, using content analysis and the aid of the NVivo 10 software. Supported by the Elisiano framework, it was found that the configuration of the Supervised Curricular Internship, whether at the university or at school, directly influences the autonomy of performance and the pedagogical practice of academics during the internship, and should be continually reassessed as a way to enable advances in future performance.Keywords: Physical Education. Professional training. Teaching.